A Comparison of Cross Training Policies in Different Job Shops - YANG, Kum Khiong (Institutional Knowledge at Singapore Management University, 2007)
This research compares a set of cross-training policies represented by different numbers of cross-trained workers, additional skills per cross-trained worker, and additional machines. The policies are evaluated in job shops, represented by different efficiency losses, labour utilization, variability in processing times, and worker absenteeism. Our results show that adding one machine in each department and cross-training one or two workers from each department with one additional skill is generally sufficient to realize most of the benefits of cross-training. Cross-training is thus beneficial in most job shops, unless the cost of the minimal training and spare machines is high. Our results also show that the value of cross-training and adding machines depends very much on the environment, and it is better to spread cross-training over more workers than to train a few workers with more skills.